Engineering circular RNA for enhanced protein production - Chen, Robert; Wang, Sean K.; Belk, Julia A.; Amaya, Laura; Li, Zhijian; Cardenas, Angel; Abe, Brian T.; Chen, Chun-Kan; Wender, Paul A.; Chang, Howard Y. (Nature biotechnology, 2023)
Circular RNAs (circRNAs) are stable and prevalent RNAs in eukaryotic cells that arise from back-splicing. Synthetic circRNAs and some endogenous circRNAs can encode proteins, raising the promise of circRNA as a platform for gene expression. In this study, we developed a systematic approach for rapid assembly and testing of features that affect protein production from synthetic circRNAs. To maximize circRNA translation, we optimized five elements: vector topology, 5′ and 3′ untranslated regions, internal ribosome entry sites and synthetic aptamers recruiting translation initiation machinery. Together, these design principles improve circRNA protein yields by several hundred-fold, provide increased translation over messenger RNA in vitro, provide more durable translation in vivo and are generalizable across multiple transgenes. Protein expression from circular RNAs is enhanced several hundred-fold by optimizing vector design.